Schwannoma of the Thoracic Esophagus - Li Poa1; Edward Ranzenbach2; David Chung2; Chirag Patel3; Michelle Min4 (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2019)
A rare tumor, esophageal schwannoma, was fi rst described by Chaterlin and Fissore in 1967 [1]. These tumors are commonly found incidentally in patients presenting with symptoms of GERD, dysphagia, or dyspnea with the fi rst evidence being an abnormal chest radiograph. Histologically the tissue presents as bundles of bland spindle cells with elongated nuclei without evidence of mitotic activity that typically appear in palisade arrangements. Stains S100 and SOX-10 are positive and STAT6 is negative. Axons are missing on neurofi lament stains. Histologically, Antoni A tissue demonstrates this palisading cellular arrangement and associated Verocay bodies refl ecting prominence of an extracellular matrix and secretion of laminin. Antoni B tissue is more loosely organized and most likely refl ects degenerated Antoni A tissue. The presence of these histological markers is indicative of a Schwannoma tumor that is amenable to excision without need of adjunctive therapy as these tumors are rarely malignant. We present the case of a 46 year old Caucasian female whose tumor was incidentally discovered during workup for surgical laminectomy.